Effects of Dietary Incorporation of Tetra (Cotinus coggygria) Extract on Immune Response and Resistance to Aeromonas hydrophila in Koi Carp (Cyprinus carpio) - Bilen, Soner; Yılmaz, Sevdan; Bilen, Aslı Müge; Biswas, Gouranga (SAABRON PRESS, 2014)
In this study, immunostimulant effects of dietary supplementation of tetra (Cotinus coggygria) extract on the non-specific immune response, and protection against Aeromonas hydrophila infection in Koi carp (Cyprinus carpio) were investigated. Koi were fed with tetra extract incorporated diets containing 0 (Control), 0.5 (Te1), 1.0 (Te2) and 1.5 g/kg (Te3), for 30 days. At the end of the study there were no differences in the values of hematological parameters between treatments. However, red blood cell counts were significantly increased (P<0.05) in Te2 group. Nitroblue tetrazolium activity was higher in all the treatment groups compared to the control, and highest values were recorded in Te3, Te1 and Te2 groups, respectively. Lysozyme and myeloperoxidase activity of the treatment groups was significantly enhanced compared to control (P<0.05), and higher values of lysozyme and myeloperoxidase activity were seen in Te3, Te2 and Te1 groups, respectively. In the challenge study with A. hydrophila (108 CFU/ml) administered after 30 days of feeding where the Koi received Te3, Te2, Te1, and control diets, they had 13.3, 20.0, 26.7, and 40.0% mortality, respectively. Tetra extract supplemented diets enhanced the immunological responses and triggered the immune system of Koi carp against A. hydrophila infection.
Keywords: hematology; Fish culture; immunostimulant; Koi carp; Fish culture--Israel; Aeromonas hydrophila; 2. Zero hunger; 3. Good health